Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd006371.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Sound therapy (masking) in the management of tinnitus in adults

Abstract: The limited data from the included studies failed to show strong evidence of the efficacy of sound therapy in tinnitus management. The absence of conclusive evidence should not be interpreted as evidence of lack of effectiveness. The lack of quality research in this area, in addition to the common use of combined approaches (hearing therapy plus counselling) in the management of tinnitus are, in part, responsible for the lack of conclusive evidence. Other combined forms of management, such as Tinnitus Retraini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 79 publications
0
109
0
4
Order By: Relevance
“…32 The individual elements have been investigated, but again the evidence base is poor. In a systematic review, the effi cacy of sound therapy approaches was inconclusive, 40 though for many clinicians the practice of fi tting hearing aids for individuals with tinnitus associated with hearing loss is axiomatic. 41 The use of wideband sound therapy devicesinitially used to cover the tinnitus completely, and hence called maskers-is similarly unsupported by evidence.…”
Section: Standard Treatmentsmentioning
confidence: 99%
“…32 The individual elements have been investigated, but again the evidence base is poor. In a systematic review, the effi cacy of sound therapy approaches was inconclusive, 40 though for many clinicians the practice of fi tting hearing aids for individuals with tinnitus associated with hearing loss is axiomatic. 41 The use of wideband sound therapy devicesinitially used to cover the tinnitus completely, and hence called maskers-is similarly unsupported by evidence.…”
Section: Standard Treatmentsmentioning
confidence: 99%
“…It can be observed from the studies that the interventions which needs highlevel evidence for establishing their efficacy are tinnitus masking, tinnitus retraining therapy, hearing aids and counselling, excluding cognitive behaviour therapy. Hobson et al 55 after reviewing six randomized controlled studies reported that tinnitus masking with hearing aids had a positive impact on a hearing handicap and overall quality of life; however, the role of each approach could not be evaluated effectively. Jastreboff 56 stressed on the effectiveness of sound therapy in tinnitus intervention, and also on the importance of hearing aids in providing sound therapy.…”
Section: Review Studiesmentioning
confidence: 99%
“…The methodological quality of treatment trials is heterogeneous in the extreme, as emphasized in all available Cochrane meta-analyses that touch on tinnitus (19)(20)(21)(22)(23)(24)(25). Accordingly, efforts are being made to improve quality standards in clinical trials of the treatment of tinnitus (25)(26)(27)(28).…”
Section: Knowledge Basementioning
confidence: 99%
“…Despite the widespread use of masking procedures, only limited data are available from controlled trials (19,30). According to a Cochrane meta-analysis, the efficacy of tinnitus masking has been neither clearly proved nor disproved (19).…”
Section: Individualized Auditory Stimulationmentioning
confidence: 99%